Demand for retakaful and reinsurance companies among takaful operators / Farhah Durar Razmi and Nur Syazreen Yusri - Razmi, Farhah Durar; Yusri, Nur Syazreen (Arshad Ayub Graduate Business School, 2018)
Insurance is an important mechanism of risk management in the organizations. However, due to the existence of the prohibited elements in its operation such as riba,gharar and maysir, insurance is considered prohibited. An Islamic alternative to insurance is takaful whose operations are based on Islamic acceptable contracts. Considering the technical similarities of takaful and insurance, a takaful company similarly needs reinsurance facilities, which in this case must be provided by retakaful companies. This research looked into the demand of retakaful or reinsurance among the takaful operators in Malaysia by looking at the current situation of takaful operator and by using the Resource Based View, Capacity Constraint Theory and Institutional Theory to identify the main factors that influence the takaful operators to cede with the retakaful or reinsurance companies. Data collection was carried out using questionnaires which were distributed to the Shariah Committee in the takaful companies and a total of 59 responses were obtained. A qualitative analysis was performed using Porter's Five Forces analysis tool and three recommendations were proposed. All the data from the questionnaire was analyze by using the SPSS Software. The findings show that only rating and size of the retakaful companies and profitability affect the takaful companies to reinsure with the retakaful companies while the other variables do not affect. Meanwhile, only one variable from reinsurance companies affects the takaful companies to reinsure with the reinsurance which is profitability.